Experience, Knowledge and Opinions Among Students about Credit Insurance - Piechota, Anna; Marczewska, Daria (Journal of Finance and Financial Law, 2017)
Credit insurance is offered to customers using bank credit. This unique insurance product is also one of the elements of bancassurance, which involves partnerships between banks and insurance companies. The purpose of this article is to identify students' awareness of credit insurance and compare the results with other studies. Based on our survey of students, opinions about credit insurance differ and the knowledge of it is insufficient, which the authors believe underlines the need for relevant education.